2019
DOI: 10.3389/fpsyt.2019.00480
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Brought Me a Lot Closer to Who I Am”: A Mixed Methods Study of Posttraumatic Growth and Positive Change Following a First Episode of Psychosis

Abstract: Background: A first episode of psychosis is often a traumatic experience that may also lead to positive change, a phenomenon that has received little attention. This knowledge gap may impede service providers’ capacity to foster positive change among service users. Objective: To investigate aspects of positive change among persons receiving early intervention services for psychosis. Design: The study objective was addressed using a mixed methods conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
3
24
0
1
Order By: Relevance
“…Indeed, even youth with serious mental disorders such as psychosis report an enhancement of their psychological well-being and personal growth following successful treatment, often in an EIP service. 25,26 Labeling and Branding Mental Health Services as "Wellness" Centers There appears to be an increasing trend to launch, what are designed and funded to be, YMH services under the title of "wellness centers or hubs". [27][28][29][30] There are possibly several reasons for such a shift of language for labeling of these services and their subsequent communication to youth seeking services for MHSU problems.…”
Section: "Wellness" In the Context Of Mental Health Services Wellnessmentioning
confidence: 99%
“…Indeed, even youth with serious mental disorders such as psychosis report an enhancement of their psychological well-being and personal growth following successful treatment, often in an EIP service. 25,26 Labeling and Branding Mental Health Services as "Wellness" Centers There appears to be an increasing trend to launch, what are designed and funded to be, YMH services under the title of "wellness centers or hubs". [27][28][29][30] There are possibly several reasons for such a shift of language for labeling of these services and their subsequent communication to youth seeking services for MHSU problems.…”
Section: "Wellness" In the Context Of Mental Health Services Wellnessmentioning
confidence: 99%
“…Based on these domains, the Post-Traumatic Growth Inventory (PTGI) was developed and validated in an initial sample population (5). Today, this inventory is used widely by researchers from different fields, on people with different kinds of trauma: survivors of natural disasters (7,8), sexual abuse (9), cancer (10), suicide survivors (11), and even psychosis (12,13). The five domains of PTGI include personal strength, new possibilities, relating to others, appreciation of life, and spiritual change (5).…”
Section: Post-traumatic Growth Entails Three Levels Of Positive Changementioning
confidence: 99%
“…In Singapore, a study on patients recovering from first episode of psychosis estimated the prevalence of PTSD at 19.7% (16). Yet, two independent studies conducted in the UK and Canada suggested that posttraumatic distress may not be the sole outcome in the aftermath of psychotic episodes (12,17).…”
Section: Post-traumatic Growth In Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Post-traumatic growth has been reported in people with rst-episode psychosis (FEP). Moderate increases in PTG have been reported (Jordan et al, 2019), with positive changes across three domains 1) intrapersonal (e.g. greater clarity of self), interpersonal (e.g.…”
Section: Introductionmentioning
confidence: 99%